Action-related eye measures to assess surgical expertise. Issue 5 (3rd September 2021) - Zheng, B; Jiang, X; Bednarik, R; Atkins, M S
Abstract: Background: Eye-tracking offers a new list of performance measures for surgeons. Previous studies of eye-tracking have reported that action-related fixation is a good measuring tool for elite task performers. Other measures, including early eye engagement to target and early eye disengagement from the previous subtask, were also reported to distinguish between different expertise levels. These parameters were examined during laparoscopic surgery simulations in the present study, with a goal to identify the most useful measures for distinguishing surgical expertise. Methods: Surgical operators, including experienced surgeons (expert), residents (intermediate), and university students (novice), were required to perform a laparoscopic task involving reaching, grasping, and loading, while their eye movements and performance videos were recorded. Spatiotemporal features of eye–hand coordination and action-related fixation were calculated and compared among the groups. Results: The study included five experienced surgeons, seven residents, and 14 novices. Overall, experts performed tasks faster than novices. Examining eye–hand coordination on each subtask, it was found that experts managed to disengage their eyes earlier from the previous subtask, whereas novices disengaged their eyes from previous subtask with a significant delay. Early eye engagement to the current subtask was observed for all operators. There was no difference in action-related fixation between experienced surgeons and novices. Disengage time was strongly associated with the surgical experience score of the operators, better than both early-engage time and action-related fixation. Conclusion: The spatiotemporal features of surgeons' eye–hand coordination can be used to assess level of surgical experience. Abstract : This study evaluated the most useful action-related eye measures for distinguishing surgeon's skill levels. Early eye disengagement from previous action was strongly associated with the surgeon's experience level, which could serve as an optimal behavioural marker for describing surgical expertise.